Patterns and drivers of regeneration of tree species in forests of peninsular Spain - Vayreda, Jordi; Gracia, Marc; Martínez-Vilalta, Jordi; Retana, Javier (Journal of Biogeography, 2013)
Aim Our study aimed to identify and explore the main factors that influence tree recruitment of multiple species at a regional scale across peninsular Spain, an understanding of which is essential for predicting future forest species composition in the face of ongoing environmental change. The study focused on the dynamics of the key transition phase from saplings to adult trees. Location The forests of peninsular Spain. Methods We used the extensive network of plots sampled in two consecutive Spanish national forest inventories (> 30,000 plots) to identify the factors that determine regeneration patterns of the 10 most abundant forest species of Spain at relatively large temporal (c. 10 years) and spatial scales (across Spain): five coniferous species of Pinus (pines) and five broadleaved species of the genera Fagus and Quercus. We fitted separate generalized linear models for the pine species and the broadleaved species to assess the response of sapling abundance and ingrowth rate to the spatial variability of climate (temperature, water availability and recent warming), forest structure (tree density, understorey and overstorey canopy cover, and basal area change) and disturbances (previous forest logging, wildfires and grazing). Results Mean sapling abundance was four times higher for broadleaved species than for pines, while mean annual ingrowth was twice as high. Sapling abundance and ingrowth rate were mainly determined by stand structure, both in pines and broadleaved trees. The direct effects of disturbances and climate were comparatively smaller, and there was no detectable effect of recent warming. Main conclusions The higher values of ingrowth rate of broadleaved species can be explained by their ability to maintain a higher sapling bank due to their greater shade tolerance. This differential response of pines and broadleaved species to canopy closure suggests a probable increase in broadleaved species at the expense of pines. This transition could occur earlier in stands with faster canopy closure dynamics. Spatially explicit, mixed-species demographic models incorporating both the ingrowth and the tree mortality components are needed for predicting the composition of future forests.
Keywords: Broadleaved trees; climate warming; conifers; disturbance; ingrowth rate; national forest inventory; sapling abundance; shade tolerance; Stand Structure; Water availability

In vitro leaf inoculation studies as an indication of tree foliage susceptibility to Phytophthora ramorum in the UK - Denman, S.; Kirk, S. A.; Brasier, C. M.; Webber, J. F. (PLANT PATHOLOGY, 2005)
Leaves of 11 coniferous and 23 broad-leaved tree species important to UK forestry were tested for their susceptibility to the quarantine pathogen Phytophthora ramorum using a detached leaf assay. Two European and two USA isolates were used. Wounded and unwounded leaves were dipped in zoospore suspensions during summer; conifers were also tested in winter. Successful infection of tissue and amount of necrosis were assessed. Highly susceptible broad-leaved hosts included Aesculus hippocastanum, Fraxinus excelsior, Quercus ilex, Ulmus procera and, to a lesser extent, Castanea sativa, Q. cerris and Q. petraea, together with Umbellularia californica and rhododendrons. Acer pseudoplatanus, Alnus glutinosa, Carpinus betulus, Corylus avellana, Fagus sylvatica, Prunus avium, Q. robur, Q. rubra and Q. suber showed consistently low susceptibility. Conifer species including Abies procera, Picea abies, P. sitchensis, Pseudotsuga menziesii, Sequoia sempervirens and Tsuga heterophylla were also susceptible. Pseudotsuga menziesii and A. procera were severely affected. Pinus contorta, P. nigra var. maritima and P. sylvestris were virtually resistant, while Taxus baccata was only slightly affected. Increased necrosis was apparent on leaves that were wounded prior to inoculation. These results extend the known range of trees that P. ramorum is able to attack and confirm its relative host-nonspecificity.
The following values have no corresponding Zotero field: pub-location: COMMERCE PLACE, 350 MAIN ST, MALDEN 02148, MA USA publisher: WILEY-BLACKWELL
Keywords: broad-leaved species; conifers; detached leaf dip assay; foliage; forest species; sudden oak death

In vitro leaf inoculation studies as an indication of tree foliage susceptibility to Phytophthora ramorum in the UK - Denman, S; Kirk, S A; Brasier, C M; Webber, J F (PLANT PATHOLOGY, 2005)
Leaves of 11 coniferous and 23 broad-leaved tree species important to UK forestry were tested for their susceptibility to the quarantine pathogen Phytophthora ramorum using a detached leaf assay. Two European and two USA isolates were used. Wounded and unwounded leaves were dipped in zoospore suspensions during summer; conifers were also tested in winter. Successful infection of tissue and amount of necrosis were assessed. Highly susceptible broad-leaved hosts included Aesculus hippocastanum, Fraxinus excelsior, Quercus ilex, Ulmus procera and, to a lesser extent, Castanea sativa, Q. cerris and Q. petraea, together with Umbellularia californica and rhododendrons. Acer pseudoplatanus, Alnus glutinosa, Carpinus betulus, Corylus avellana, Fagus sylvatica, Prunus avium, Q. robur, Q. rubra and Q. suber showed consistently low susceptibility. Conifer species including Abies procera, Picea abies, P. sitchensis, Pseudotsuga menziesii, Sequoia sempervirens and Tsuga heterophylla were also susceptible. Pseudotsuga menziesii and A. procera were severely affected. Pinus contorta, P. nigra var. maritima and P. sylvestris were virtually resistant, while Taxus baccata was only slightly affected. Increased necrosis was apparent on leaves that were wounded prior to inoculation. These results extend the known range of trees that P. ramorum is able to attack and confirm its relative host-nonspecificity.
Keywords: broad-leaved species; conifers; detached leaf dip assay; foliage; forest species; sudden oak death